2019
DOI: 10.3389/fped.2019.00335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Allostatic Load as a Marker of Chronic Stress in Children and the Importance of Excess Weight

Abstract: Introduction: Allostatic load (AL) refers to the physiological response associated with the burden of chronic stress. Excessive weight is an important source of physiological stress that promotes a detrimental chronic low-inflammation state. In order to define a correlation between cumulative biological dysregulation and excess weight, we measured AL scores in a pediatric population. Patients and Methods: We enrolled 164 children and adolescents (11.89 ± 3.89). According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…We surmise that in terms of metabolic health it appears as insufficient to consider "obese" and "non-obese" children as a dichotomous condition. Instead, the ideal "wellness state" should therefore include a much more refined evaluation of body composition and adipose tissue distribution along with a combination of several non-overlapping biomarkers that would include CP [17]. Indeed, circulating CP is not only a biomarker of inflammation but also in its protein complex state as a dimer stimulates the recruitment and activation of neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We surmise that in terms of metabolic health it appears as insufficient to consider "obese" and "non-obese" children as a dichotomous condition. Instead, the ideal "wellness state" should therefore include a much more refined evaluation of body composition and adipose tissue distribution along with a combination of several non-overlapping biomarkers that would include CP [17]. Indeed, circulating CP is not only a biomarker of inflammation but also in its protein complex state as a dimer stimulates the recruitment and activation of neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Ulna length was measured from the tip of the olecranon process to the tip of the styloid process. Data corresponding to the average of the ulna measurements and tibia lengths were used to obtain an estimate of stature according to specific equations [12] In children with obesity, anthropometric measurements were performed as previously reported [4].…”
Section: Anthropometric Parameters and Blood Pressurementioning
confidence: 99%
“…As this was a pilot study, the only required baseline characteristic for all participants was that they identified as either TGE for the study population or cisgender for the control population. However, patients with preexisting chronic conditions, including obesity (BMI>95%), chronic kidney disease stage 3 or higher, liver disease, chronic infections such as hepatitis B, hepatitis C, HIV, tuberculosis, or autoimmune disorders such as systemic lupus erythematosus or primary immunodeficiency, receiving treatment with steroids, or current smokers will be excluded from the study because these conditions and medications or habits may alter levels of stress and inflammatory biomarkers [43][44][45]. We will also focus recruitment efforts on patients who have not initiated hormone therapy, although this will not be a requirement.…”
Section: Study Participants and Sitesmentioning
confidence: 99%